Efficacy of Pulsed Radiofrequency on Cervical 2-3 Posterior Medial Branches in Treating Chronic Migraine: A Randomized, Controlled, and Double-Blind Trial. (11th June 2015) - Yang, Yuecheng; Huang, Xuehua; Fan, Yinghui; Wang, Yingwei; Ma, Ke
Abstract : Objective . The aim of this study was to examine the efficacy and safety of pulsed radiofrequency (PRF) in the treatment of chronic migraine (CM) on cervical 2-3 posterior medial branches. Methods . This randomized, double-blind, and controlled clinical trial included 40 subjects with CM, who were randomly divided into two groups: treatment (treated by PRF) and sham (treated by sham treatment). Pain intensity, headache duration (days), the Migraine Disability Assessment Questionnaire (MIDAS), and aspirin dose taken by patients were evaluated at 1, 2, and 6 months after the intervention. Side effects were observed from the time of treatment and throughout the follow-up period. Results . During the follow-up, pain intensity, headache duration (days), disability score, and the analgesic dose were significantly improved in the treatment group compared to the sham group (P < 0.001 ) and the baseline (P < 0.001 ) at all measured time points after intervention. No serious complications were reported. Conclusion . PRF on the cervical 2-3 posterior medial branches could provide satisfactory efficacy in the treatment of CM without obvious adverse effects.